The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/poms.13094
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Quality‐Distribution Information for the Selective Assembly of Intermediary Components in the Automotive Industry

Abstract: T his study investigates the value of a supplier sharing information about the quality-distribution (i.e., dimensional mean or variance) of components with an assembler who matches such parts with the selective assembly of an intermediary component. Selective assembly is a strategy that is widely used by high-precision manufacturing companies to gain a competitive advantage in product quality. The use of inexpensive intermediary components (e.g., bearings) to ensure that all mating components are matched with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Information about both σy2 and μy values was more valuable for FBSA than information about only μy, which in turn was more valuable than information about only σy2. Clottey and Benton (2020) obtained a similar result in a different selective assembly context, when the focus was safety‐stock reduction due to shared information. The current study indicates that this result also applies to FBSA with matchable degree as a criterion.…”
Section: Case Analysismentioning
confidence: 79%
See 3 more Smart Citations
“…Information about both σy2 and μy values was more valuable for FBSA than information about only μy, which in turn was more valuable than information about only σy2. Clottey and Benton (2020) obtained a similar result in a different selective assembly context, when the focus was safety‐stock reduction due to shared information. The current study indicates that this result also applies to FBSA with matchable degree as a criterion.…”
Section: Case Analysismentioning
confidence: 79%
“…To determine the benefit of receiving information about μy, σy2, or both from the RB supplier, we adopted a Bayesian lens. A Bayesian approach to evaluating the impact of shared information has a firm grounding in statistical decision theory (Raiffa and Schlaifer 1959) and has likewise been employed in other studies (Clottey and Benton 2020, Eppen and Iyer, 1997, Milner and Kouvelis 2002) involving the effect of shared information on predicted quantities. In this study, we want to evaluate the impact of shared information, vs. using just historical data, to estimate the mean and/or variance of incoming part dimensions.…”
Section: Model Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive review of this stream of literature can be found in Guan and Chen (2015). Arya et al (2014), Clottey andBenton (2020), andGuan et al (2020) also consider the disclosure and sharing of quality information. Kuksov and Lin (2010) develop a game-theoretic model and examine the interaction of information provision, product quality, and pricing decisions by competitive firms.…”
Section: Literature Reviewmentioning
confidence: 99%